Synergy In The Utilization Of Productive Zakat: A Case Study Of Baznas And The Provincial Government Of Bengkulu - Apriani, Laisah; Arisandy, Yosy; Nurhab, Badaruddin (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study investigates the synergy between BAZNAS and the Provincial Government of Bengkulu in utilizing productive zakat through the Business Cart Assistance Program to empower mustahik economically. Methodology: A descriptive qualitative approach was employed, using interviews, observations, and document analysis. Data were validated through triangulation and trustworthiness criteria such as credibility, transferability, and confirmability. Results: From 2021–2024, 60 business carts were distributed, leading to increased income for many beneficiaries. Institutional synergy enabled efficient targeting, planning, and fund utilization. Findings: Despite positive outcomes, challenges included low entrepreneurial motivation, misuse of carts, and weak monitoring. Some recipients abandoned or misused the assistance. Novelty: The study uniquely explores productive zakat implementation through local government collaboration—a rarely documented model. Originality: This is among the first studies evaluating a zakat-based empowerment model integrating formal government roles at the provincial level. Conclusions: The program enhances economic independence among mustahik but requires stronger regulations, entrepreneurship training, and consistent monitoring to ensure sustainability. Type of Paper: Empirical research paper using a qualitative case study method.